2013
DOI: 10.1001/jamasurg.2013.623
|View full text |Cite
|
Sign up to set email alerts
|

FFP:RBC Resuscitation Ratio and Post-Shock Fluid Uptake

Abstract: The severity of shock is best predicted by shock time and the RBC, FFP, and BES infusions in the OR. Contrary to recent reports, the FFP:RBC ratio in the OR correlates directly with duration and BES needs of phase 2, whereas the BES:RBC ratio correlates inversely with phase 2 duration and BES needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The major adverse effects of CLS include alveolar edema, restricted gas exchange and hypoxia, all of which aggravate injuries to the capillary endothelium cause edema in major organs such as the brain, the heart, the liver and the kidneys with the structures and functions that are damaged and that ultimately result in multiple organ dysfunction syndromes (MODS). Once that happens, the patient’s condition becomes more serious and includes higher risk for death [7]. Therefore, investigating the pathogenesis of vascular leakage or increased capillary permeability is of great significance for the prophylaxis and treatment of CLS.…”
Section: Introductionmentioning
confidence: 99%
“…The major adverse effects of CLS include alveolar edema, restricted gas exchange and hypoxia, all of which aggravate injuries to the capillary endothelium cause edema in major organs such as the brain, the heart, the liver and the kidneys with the structures and functions that are damaged and that ultimately result in multiple organ dysfunction syndromes (MODS). Once that happens, the patient’s condition becomes more serious and includes higher risk for death [7]. Therefore, investigating the pathogenesis of vascular leakage or increased capillary permeability is of great significance for the prophylaxis and treatment of CLS.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in the abdomen, it aggravates retroperitoneal edema and ascites that raise intra-abdominal pressure which is the major cause of death in ACS. [ 1 , 8 , 11 ] In our case, the intravenously infused crystalloid volume (approximately 4500 mL before surgery) was not enough to cause fatal pulmonary edema and ACS. Studies have shown that the administration of more than 5000 mL of crystalloid within 24 h is one of the independent risk factors for secondary ACS, and more than 7000 mL of crystalloid increases the risk of fatal pulmonary edema.…”
Section: Discussionmentioning
confidence: 67%
“…Sepsis can increase cell permeability, and lead to capillary leakage syndrome (CLS), which causes severe hypoproteinemia, hypovolemia, tissue hypoperfusion, edema, shock and multiple organ dysfunction syndrome [22][23][24]. Our previous studies have shown that TH can improve the permeability of septic cells [7].…”
Section: Discussionmentioning
confidence: 99%